Topper [videorecording (DVD)] - McNarmara, Kevin; O'Brien, Mark, 1984-; Callen, Bryan; Clayton, Amanda (Deskpop Entertainment, 2025)
Once a top comedian, Topper has fallen from grace and is now a bitter hack in LA's comedy scene. A ghost from his past and a friend's push force him to return to Detroit to confront his demons before he loses his dream and himself forever.